Internet Use and its Relationship to Economic Growth: Analysis for Nicaragua - Brenes - González, Humberto Antonio (Universidad Francisco de Paula Santander, 2023)
In recent years the Internet has played an important role in the dynamics of the economy of the countries, for this reason, the present work called "The use of the Internet and its relationship with economic growth: Analysis for Nicaragua" had as objective to establish the relationship that exists between the use of the Internet and economic growth for Nicaragua. The model established to determine the relationship between the variables was under a quadratic model, which had economic growth as a dependent variable, measured by Gross Domestic Product (GDP), at constant prices in 2018 dollars and as an independent variable, at percentage of the population that uses the Internet. The results obtained under the proposed quadratic model were statistically significant, which validates and evidences the existence of a strong relationship between the variables under study, with its correlation coefficient being 98.21% and the determination coefficient being 96.46%.